Numerical Analysis of Turbulent Flow through a Ducted Propeller: Numerical Analysis of Turbulent Flow through a Ducted Propeller - Bangalee, Md Zavid Iqbal; Ahmed, Tausif; Saha, Kajal Chandra (Dhaka University Journal of Science, 2025)
The current world of air travel has become significantly option-heavy over the past few decades. There are commercial jet-liners, helicopters, and private jets. In all these advancements in air travel, one aspect has always been of significant importance: ducted-propelled aircraft. A duct, though simple in form, can lead to an increase in the efficiency of an aircraft. The position of the duct, its thickness, its radius, and the material it has been made of all play essential roles in nominating a certain duct for a specific aircraft. In this study, the numerical analysis of turbulent flow through a ducted propeller will be observed, and different aerodynamic coefficients will be computed. This study will show that a ducted propeller is capable of producing significant lift for an automatic or manual aircraft to fly through turbulence. Dhaka Univ. J. Sci. 73(2): 119-126, 2025 (July)